Improving Disability Independence Through Assistive Device Distribution Programs in Surabaya City - Andi Galih Waskito; Wardaya, Wirya; Martha Hendrati, Ignatia (Unram Journal of Community Service, 2025)
Persons with disabilities in Indonesia still face significant challenges in achieving independence due to discriminatory views and limited access to various services, including assistive devices. In Surabaya City, with a substantial number of persons with disabilities, the Social Services Department of Surabaya City, through its social rehabilitation program, strives to improve their quality of life by distributing assistive devices. This program involves systematic stages, starting from receiving reports, conducting field surveys, measuring assistive devices, to distributing aid to recipients in need. The program successfully distributed various assistive devices, such as wheelchairs, hearing aids, and prosthetic limbs, with a total of 254 units during the writer's internship period (September 23 - December 31, 2024). As a result, recipients demonstrated significant improvements in independence, both in carrying out daily activities and in interacting with others. Additionally, the families of the recipients also experienced benefits in the form of reduced burdens, as family members who were previously fully dependent now have greater abilities to manage their own needs. This program is expected to continue to grow and provide further solutions to help build an inclusive and empowered society for persons with disabilities in Surabaya.